Methane potential from fish oil byproducts. Anaerobic digestion of spent bleaching earth and glycerin - Hafliði Ásgeirsson 1990- (2015)
Biogas production in Iceland is quite underdeveloped. The industry currently seeks to find organic substrates suitable for biogas production. Spent bleaching earth and glycerin, both by-products from the fish oil refining industry, were co-digested with manure in anaerobic conditions in a batch assay method. The bleaching earth was mixed with manure in the ratio 5% and 10% w/w. Glycerin was mixed with manure in the ratio 1.5% and 3% w/w. Biogas volume was measured over a period of 90 days for SBE and 40 days for glycerin. Results show that methane yield in co-digestion with manure for spent bleaching earth was highest at 390ml/gVS and 447ml/gVS for glycerin. Additionally, instruments for experiments in a continuous reactor was constructed. The setup was composed of three bioreactors with 4 liter total volume and 3 liter working volume. The vessels were combined with an automatic gas volume analyzer that measures gas production automatically. The equipment was run for 30 days, and data collected for 10 days. Anaerobic digestion was present at the starting phase, but further running is needed before a full steady baseline. Lífgas framleiðsla á Íslenskri grundu er frekar vanþróaður iðnaður. Eins og staðan er í dag þá er iðnaðurinn að leitast eftir auknu magni af lífrænum efnasamböndum sem hentað gætu í slíka framleiðslu. Bleiki jarðvegur (e. bleaching earth) og glýserín, bæði aukaafurðir frá lýsisframleiðslu, voru sam-melt með mykju við loftfirrtar aðstæður í lotuframleiðslu tilraun. Bleiki jarðvegurinn var blandaður með mykju í hlutfallinu 5% og 10% bleiki jarðvegur móti 95% og 90% mykju miðað við massa. Glýserín var blandað með mykju í hlutfallinu 1.5% og 3% miðað við massa. Lífgas var rúmmáls mælt yfir 90 daga tímabil fyrir bleiki jarðveg, og 40 daga tímabil fyrir glýserín. Bestu niðurstöður sýna fram á metanmagn fyrir bleiki jarðveg fengust við 10% hlutfall, en magn metans miðað við rokgjarnt fast efni var um 390ml/gVS. Fyrir glýserín fékst metanmagn miðað við rokgjarnt fast efni 447ml/gVS, en fékkst það við ...